POTENSI PRODUKSI TANDAN BUAH SEGAR TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq) PADA 3 (TIGA) JENIS TANAH DI LAHAN PERKEBUNAN PT. MITRA BANGGA UTAMA: POTENTIAL OF PRODUCTION OF FRESH FRUIT FRUITS OF OIL PALM (Elaeis guineensis Jacq) IN 3 (THREE) TYPES OF SOIL IN PLANTATION LAND PT. MITRA BANGGA UTAMA - Efta Liwi; Akhmad Sopian; Zainudin (Universitas Widya Gama Mahakam, 2021)
Palm oil is one of the plantation commodities that contributes as a reliable contributor to foreign exchange. The raw materials produced from oil palm trees include palm oil, palm kernel oil, and palm kernel pulp. Each product has a commercial value, but of the three products that currently have potential is palm oil, better known as CPO (Crude Palm Oil). The ever-increasing world consumption of palm oil makes companies or plantations that cultivate palm oil have to work hard to meet the needs of palm oil. The increase in oil palm production was due to the expansion of oil palm plantation areas. oil palm results in lost opportunities to achieve yields that meet crop productivity standards. The productivity of oil palm plants varies greatly according to environmental conditions (climate, land conditions), genetic conditions (plant material and plant age), and the interaction between the two in the technical form of culture implementation. This study aims to determine the production of fresh fruit bunches (FFB), the average weight of bunches (BJR), and the number of bunches per TPH on that type of soil. This research was conducted in the oil palm plantation of PT. Mitra Proud Utama is located in Anggana District, Kutai Kartanegara Regency. Based on the results of the research on the potential production of fresh fruit bunches on three types of soil, it was shown that soil type did not affect the number of bunches and flowers. The production of the best number of bunches and flowers was on entisol soil of 10.00 bunches/tree, spodosol soil of 9.98 bunches/tree, and ultisol of 8.85 bunches/tree. Soil type has a significant effect on the average bunch weight and the best BTR on 10.77 kg ultisol soils, 9.79 kg on spodosol soils, and 9.17 kg on entisol soils and has not reached the S3 land class standard. Potential Number of bunches per The best TPH was on ultisol soil (yellow) 23.7 bunches/TPH.